Qur’an-Based Spiritual Education: A Study of the Concept of Asy-Syifa’ in the Formation of Muslim Personality - Andi Bangsawan Tolere; Muhsin Muhsin; Mardan Mardan (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study aims to analyze the concept of Asy-Syifa’ in the Qur'an through a thematic (tafsir maudhu’i) approach by identifying relevant verses, examining their linguistic meanings, analyzing their contexts of revelation (asbab al-nuz?l), exploring the views of classical and contemporary Qur'anic exegetes, and formulating a comprehensive understanding of Qur'anic healing. This research employed a qualitative approach using library research. The data were collected from the Qur'an, classical and contemporary books of tafsir, hadith collections, academic books, and peer-reviewed journal articles relevant to the study. The data were analyzed using content analysis through data reduction, data categorization, comparative interpretation, and conclusion drawing. The findings demonstrate that the concept of Asy-Syifa’ in the Qur'an extends beyond physical healing to include the purification of the heart, psychological tranquility, spiritual guidance, social reconciliation, and natural healing through lawful means such as honey. The Qur'an positions Allah as the ultimate source of healing, while medical treatment, natural remedies, and spiritual practices function as legitimate means (asbab) within the divine order. Furthermore, the effectiveness of Qur'anic healing is closely associated with faith, sincerity, and obedience to divine guidance. This study contributes to the development of Qur'anic studies by presenting a holistic framework of Asy-Syifa’ that integrates theological, educational, psychological, and social perspectives, thereby offering a broader understanding of healing within contemporary Islamic scholarship.